Main Methodological Approaches to Creating Inclusive and Gender Sensitive Education Environment in Institutions of Vocational (Technical and Vocational) Education - Liesnikova, М. V. (Statistics of Ukraine, 2021)
The opportunity to develop the competencies required for the full-fledged involvement in the community life, the active citizenship and the contribution to the economic development of the country is an inherent right of each person irrespective of gender, origin or talents. The vocational (technical and vocational) education (V(TV)E) offers a human these possibilities and helps realize his/her economic and social potentials. The inclusive education is a system of education services guaranteed by the state and based of the principles of non-discrimination, consideration for the human’s versatility, effective and inclusive participation of all the persons involved in the education process. Creating the inclusive and gender sensitive education environment in V(TV)E institutes in the context of the continuous life-long education is a strategic objective of each civilized country. This environment should be built on the following components: legal support; forecasting of the required competencies; achievement of gender equality; assurance of the education quality and relevance; achievement of the universal design; specification of the inclusive education techniques on the gender equality foundations used by V(TV)E institutions in the education process, and monitoring. The author developed a toolkit for a monitoring study of the abovementioned techniques used by V(TV)E institutions in the context of the continuous life-long education. The questionnaire designed for vocational instructors contain 37 statements and consists of the three components in creating the inclusive and gender sensitive education environment in a V(TV)E institution: (i) component A “Development of the organizational culture in a V(TV)E institution”; (ii) component B “Internal policy”; (iii) component C “Implementation of the inclusive practice. Learning of inclusive education techniques on the gender equality foundations”. Each component contains two modules. The questions are built using Likert scale. The monitoring will allow for obtaining the data reflecting peculiar features of implementing inclusive education techniques in students’ and participants’ training as part of the continuous life-long education. Results will allow to assess the development of organizational culture in V(TV)E institutions as the background for creating teams which collaborative achievements are based on the recognition of each member’s value; analyzing internal policies of V(TV)E institutions from the perspective of the inclusion of each student irrespective of age, gender or specific individual demands; setting up strategies for reforms in V(TV)E institutions, intended to create the inclusive education environment; finding out what techniques of inclusive education on the gender equality basis are used by lecturers of V(TV)E institutions in organizing the education process in order to build the inclusive and gender sensitive education environment in the context of the continuous life-long education; identifying the factors impeding the creation of such education environment; to check the readiness of vocational training instructors in V(TV)E institutions for work with students with special education needs.